Identifying and Managing Impacts of Point and Non-Point Source Pollution on Surface Water Quality - Malone, Patrick R. (Worcester Polytechnic Institute, 2015)
Surface waters can be impacted by point and non-point source (NPS) pollution including stormwater culverts, runoff, and septic systems. It is important to develop water quality monitoring plans that can be implemented within resource constraints while still providing useful data. The goal of this research was to develop a sampling strategy to identify the impacts of point and NPS pollution on surface waters. This research incorporates water quality monitoring, land use data, precipitation data, and statistical modeling to improve understanding of pollutant impacts on surface waters. Research was conducted at a 152-acre private lake in western Massachusetts. Lake water samples were collected approximately twice per month over 12 months at ten sample locations selected to isolate land uses, including (1) shoreline samples adjacent to homes with septic systems, (2) shoreline samples at stormwater discharge sites, and (3) control samples at the lake influent, lake effluent, and a private beach. Sampling events included dry and wet weather conditions. Water samples were analyzed for physical, chemical, and microbiological parameters including: pH, conductivity, dissolved oxygen, turbidity, alkalinity, nutrients, anions, organic carbon, and microbial indicators (total coliform, E. coli, enterococci, male-specific and somatic coliphages). The data were statistically analyzed to determine how land use, season, and precipitation affect the risk of contamination to surface waters. Results indicated significant water quality variations by land use, season, and precipitation and identified important correlations between water quality parameters.
Keywords: Water Quality